Histone deacetylases: potential therapeutic targets for idiopathic pulmonary fibrosis - Cheng, Hai-peng; Jiang, Shi-he; Cai, Jin; Luo, Zi-qiang; Li, Xiao-hong; Feng, Dan-dan (Frontiers in Cell and Developmental Biology, 2024)
Idiopathic pulmonary fibrosis (IPF) is a chronic progressive disease of unknown origin and the most common interstitial lung disease. However, therapeutic options for IPF are limited, and novel therapies are urgently needed. Histone deacetylases (HDACs) are enzymes that participate in balancing histone acetylation activity for chromatin remodeling and gene transcription regulation. Increasing evidence suggests that the HDAC family is linked to the development and progression of chronic fibrotic diseases, including IPF. This review aims to summarize available information on HDACs and related inhibitors and their potential applications in treating IPF. In the future, HDACs may serve as novel targets, which can aid in understanding the etiology of PF, and selective inhibition of single HDACs or disruption of HDAC genes may serve as a strategy for treating PF.